An Artificial Intelligence System to Predict Quality of Service in Banking Organizations - Castelli, Mauro (2019)
Castelli, M., Manzoni, L., & Popovič, A. (2016). An Artificial Intelligence System to Predict Quality of Service in Banking Organizations. Computational Intelligence And Neuroscience, 2016, [9139380]. https://doi.org/10.1155/2016/9139380